(untitled) (Conversatoria Linguistica, 2019)
Ambiguity is the most often used linguistic phenomenon applied in creating jokes, both at present, and several dozen years ago. The article describes comical texts printed in the widely-read satiric weekly magazine “Wolna Myśl, Wolne Żarty”, which was publishing in Łódź from 1919 to 1939, and in detail shows jokes utilized lexical and syntactical polysemy.